1996
DOI: 10.1117/12.260771
|View full text |Cite
|
Sign up to set email alerts
|

<title>Multi-course PDT of malignant tumors: the influence on primary tumor, metastatic spreading and homeostasis of cancer patients</title>

Abstract: The first clinical trials of photodynamic therapy (PDT) of cancer with two photosensitizers, PHOTOHEME and PHOTOSENS, were started in P.A.Hertzen Research Oncological Institute (Moscow, Russia) in 1992 and 1994 {1,2}. Up to now, 208 patients with primary, recurrent and metastatic malignant tumours (469 ) of skin (34 patients/185 tumours), breast cancer (24/101), head and neck (30/31), trachea and bronchus (31/42), esophagus (35/35), stomach (31/32), rectum (4/4), vagina and uterine cervix (7/8) and bladder (12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Photogem is the most used photosensitizer in Brazil [5,6]. These three HpD are believed to present chemical and photophysical characteristics and diagnostic and therapeutic features identical to PF [7,8]. However, recent studies have shown that they are in fact different in its photostability [9] and degradation behavior [10,11], cytotoxicity in several tumor and non-tumor cell lines [9,10,12], threshold dose [13], and depth of necrosis [13].…”
Section: Introductionmentioning
confidence: 99%
“…Photogem is the most used photosensitizer in Brazil [5,6]. These three HpD are believed to present chemical and photophysical characteristics and diagnostic and therapeutic features identical to PF [7,8]. However, recent studies have shown that they are in fact different in its photostability [9] and degradation behavior [10,11], cytotoxicity in several tumor and non-tumor cell lines [9,10,12], threshold dose [13], and depth of necrosis [13].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the wavelength enables greater penetration of light into tissues [12]. Photogem , a photosensitizer produced in Russia and utilized in Brazil, has identical chemical, photophysical, diagnostic and therapeutic characteristics to Photofrin [13][14][15][16][17]. As Photofrin [18][19][20], Photogem consists of a mixture of monomers, dimmers, and oligomers of hematoporphyrin derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Photofrin 1 is being investigated as a possible therapy for a number of other malignant and non-malignant conditions. Other hematoporphyrin derivatives are also being used, with Photoheme, an enriched hematoporphyrin derivative similar to Photofrin 1 accepted for clinical use in Russia for easily accessible cancers including skin, breast, oropharingeal, lung, larynx and gastrointestinal cancers along with psoriasis and prophylaxis for corneal transplant opacity and recurrent blindness, where newly formed blood vessels result in loss of corneal transparency [23][24][25][26].…”
mentioning
confidence: 99%